2010
DOI: 10.1016/j.ijhydene.2010.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment on Pt–Co/C cathode catalysts for the oxygen reduction reaction

Abstract: 8035078560Carbon supported Pt and Pt-Co electrocatalysts for the oxygen reduction reaction in low temperature fuel cells were prepared by the reduction of the metal salts with sodium borohydride and sodium formate. The effect of surface treatment with nitric acid on the carbon surface and Co on the surface of carbon prior to the deposition of Pt was studied. The catalysts where Pt was deposited on treated carbon the ORR reaction preceded more through the two electron pathway and favored peroxide production, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…For instance, a variety of Pt alloy nanomaterials has been developed to enhance its MOR activity considering the alloy effect, such as PtCu nanoparticles [7], PtRu nanotubes [8], supported PtRu nanoparticles [9e11], PtAu [12] and PtPd [13] nanoparticles and so on. Recently, non-precious 3d transition metals (referring to the unfilled subshell electrons in the 3d-orbital), such as Fe, Co, and Ni, were found to have great synergistic catalytic effect on the MOR activity of Pt [13e16] besides their remarkably synergistic role on oxygen reduction reaction (ORR) [5]. With the advantages of the activity enhancement and the cost reduction by alloying with the 3d metal, the morphology of these alloy nanomaterials has also attracted great attention by virtue of the structure effect [6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a variety of Pt alloy nanomaterials has been developed to enhance its MOR activity considering the alloy effect, such as PtCu nanoparticles [7], PtRu nanotubes [8], supported PtRu nanoparticles [9e11], PtAu [12] and PtPd [13] nanoparticles and so on. Recently, non-precious 3d transition metals (referring to the unfilled subshell electrons in the 3d-orbital), such as Fe, Co, and Ni, were found to have great synergistic catalytic effect on the MOR activity of Pt [13e16] besides their remarkably synergistic role on oxygen reduction reaction (ORR) [5]. With the advantages of the activity enhancement and the cost reduction by alloying with the 3d metal, the morphology of these alloy nanomaterials has also attracted great attention by virtue of the structure effect [6].…”
Section: Introductionmentioning
confidence: 99%
“…The power density of individual electrocatalysts was significantly improved compared to the past reports on the same electrocatalysts synthesized by other methods. [30][31][32][33] We believe that the improvement in fuel cell performance was due to enhanced EASA of the electrocatalysts that resulted due to the prevention of aggregates and overall lower size (3-15 nm) of Pt nanoparticles.…”
Section: Pem Fuel Cell Performancementioning
confidence: 99%
“…46,47 Fox and Colon-Mercado synthesized carbon supported Pt and PtCo electrocatalysts for ORR by the reduction of the metal salts in the presence of sodium borohydride and sodium formate. 48 They pointed out that addition of Co increased electrocatalytic activity and active surface area when used with sodium borohydride as a reducing agent as compared to sodium formate. Kumar et al demonstrated sonochemical preparation of carbon supported PtCo/C bimetallic electrocatalysts having particle size smaller than 5 nm.…”
Section: Introductionmentioning
confidence: 99%